Methane Emission Estimation and Dispersion Modeling for a Landfill in West Java, Indonesia - Soni Pratamayudha Wijaya; Siti Ainun; Didin Agustian Permadi (Journal of the Civil Engineering Forum, 2021)
Methane gas (CH4) is a greenhouse gas that can potentially induce global warming and it is known as surface ozone precursor. CH4 is generally produced from biological process occurred at the landfill which is not equipped with CH4 recovery and treatment system. Note that, very few of landfills in Indonesia have been operated as sanitary landfill but rather most of them act as dumping site. One landfill in West Java Province is Sarimukti Landfill which receives nearly 604,674 ton of solid waste annually. Existing studies have been using the first tier of the Intergovernmental Panel on Climate Change (IPCC) guideline for the emission estimation which provides high uncertainty due to the international default data. In addition, there are uncertainties for the multi years estimation because the kinetic rate of biological processes was not involved in the calculation. To fill in this gap, this research was conducted to use an alternative of methodology for estimating CH4 from landfill using a well known software of the Landfill Gas Emissions Model (LandGEM) which facilitates biological reaction in the calculation. We will also perform calculations using the traditional IPCC method for the Sarimukti landfill as a case study. To quantify the impact of CH4 emission, its dispersion was calculated using the AMS/EPA Regulatory Model (AERMOD). Potential impact on surface ozone formation was assessed using ozone formation potential (OFP) metric. The results of this study indicate that methane gas emissions have increased every year, where the highest emissions occurred in 2025 of 14,810.41 Mg/year (LandGEM) and 11,462.66 Mg/year (IPCC). Likewise, the potential for OFP from methane gas concentrations has increased every year where the highest concentration of surface ozone formation is in 2025 of 183,40 Mg/year. Meanwhile, the methane emission (CH4) has a dispersion pattern which is influenced by meteorological factors around the Sarimukti landfill.